1989
DOI: 10.1111/j.1476-5381.1989.tb11989.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic muscarinic receptors inhibiting endogenous noradrenaline release in the portal vein of the freely moving rat

Abstract: 1 In the portal vein of the freely moving unanaesthetized rat, the existence of presynaptically located inhibitory muscarinic receptors was investigated by use of the muscarinic agonist methacholine (MCh) 2 Infusion of MCh (0.3pgmin-1) did not significantly inhibit the endogenous noradrenaline (NA) overflow in portal plasma. However, after inducing high intra-synaptic concentrations of NA by blocking the presynaptic a2-adrenoceptors with yohimbine (lmgkg-1), MCh (0.3jpgmin-1) was able to reduce the yohimbine-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recently we showed, with freely moving, unanaesthetized, permanently cannulated rats (Remie & Zaagsma, 1986;Remie et al, 1988), a MCh-induced inhibition of NA overflow during electrical stimulation of the portal vein nervous plexus. This inhibition could be reversed to control values by using the non-selective muscarinic antagonist atropine, indicating the muscarinic nature of these inhibitory presynaptic receptors (Remie et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently we showed, with freely moving, unanaesthetized, permanently cannulated rats (Remie & Zaagsma, 1986;Remie et al, 1988), a MCh-induced inhibition of NA overflow during electrical stimulation of the portal vein nervous plexus. This inhibition could be reversed to control values by using the non-selective muscarinic antagonist atropine, indicating the muscarinic nature of these inhibitory presynaptic receptors (Remie et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…The pIC50 values of the antagonists for muscarinic receptors in the portal vein were calculated as the -log of the portal vein concentration (molar) of the antagonist causing 50% inhibition of the MCh-induced decrease of electricallyevoked NA overflow. Atropine (0.6mgkg-1), administered 15min before stimulation, was used in separate experiments to determine the maximal amount of electrically-evoked NA overflow in the presence of an antagonist; this was 122 + 8% of the control stimulation value which indicates a minor inhibition of NA overflow by endogeneous acetylcholine, released during co-stimulation of cholinergic neurones (Remie et al, 1989). To allow calculation of the pIC50 values this maximal effect was used for all the selective antagonists and the least square regression line analysis was used to determine the concentration needed to obtain 61% (pIC50) of the maximal effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this model, prejunctional receptor-induced changes in evoked endogenous noradrenaline overflow in the portal vein of freely moving rats can be studied. Several prejunctional receptor systems have now been investigated with this model and shown to have pronounced capacities to modulate vascular noradrenaline overflow in vivo (Remie et ai., 1988;Remie, Coppes & Zaagsma, 1989;Remie, Coppes, Meurs, Roffel & Zaagsma, 1990a;Coppes, Smit, Nashid Khali, Brouwer & Zaagsma, 1993). Problems, however, may arise when the drugs used possess not only a presynaptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information available about the pharmacodynamic profiles of this drug in volunteers and hypertensive patients. In animal experiments it has been demonstrated that nebivolol has a presynaptic effect on the release of noradrenaline in the conscious rat [2] and induces a reduction of total peripheral vascular resistance (TPVR) in anesthetised dogs, even in low doses [3].…”
mentioning
confidence: 99%